Use of waste from the sugar alcohol industry for the production of okra seedlings (Research, Society and Development, 2020)
The filter cake is a residue from the sugarcane processing industry and has shown excellent results for its use in fertilizing agricultural crops. The objective of this work was to evaluate the growth and development of okra seedlings produced with different proportions of filter cake as a substrate. The experiment was carried out under greenhouse conditions in a completely randomized design (CRD) with five treatments and five replicates (5x5). The treatments consisted of five proportions for filling the tubes with 0, 25, 50, 75 and 100% filter cake. The filter cake was obtained in a sugar and alcohol industry near the municipality of Santa Helena de Goiás. Were evaluated plant height (PH), stem diameter (SD), number of leaves (NL), root length (RL), aerial fresh mass (AFM), fresh root mass (FRM), aerial dry mass (ADM) and the dry root mass (DRM). The data were submitted to analysis of variance by the F test (p